The Relationship Between Remote Work and Employee Productivity in A Tech Company - Prajwalita Khaira Adindatarisa; Achmad Fajar Hendarman (Green Publisher Indonesia, 2025)
This study addresses the impact of remote work on employee productivity within a tech company setting specializing in software development and IT Condulting called PT. HLM. PT. HLM has adopted and implemented remote work setting for the past five years since 2020. The study will focusing on three key independent variables: Work Autonomy, Collaboration Quality, and Work Environment. The research is motivated by the growing adoption of remote work models and the need to understand factors that influence productivity in such settings. The background highlights challenges such as maintaining effective communication, managing flexible work hours, and ensuring conducive home workspaces. The subject of this study is PT. HLM, a technology company at Indonesia. As the subject of this study, PT. HLM has implemented a full Remote work setup for the last 5-6 years, aiming to maintain employee productivit. However, based on group discussion between Project Managers and Leaders in PT. HLM with researchers there are several obstacles in the beginning. Grounded in Self-Determination Theory, Media Richness Theory and Environmental Psychology. Self-Determination theory emphasizes that autonomy enhances motivation and competence, which are crucial for productivity. Media richness theory suggests that richer communication media are more effective for collaboration than lean media like text based, environmental psychology highlights the importance of structured and distraction free work environment for maintaining productivity. The study uses approach of quantitave survey data from 50 employees. The survey measures work autonomy, collaboration quality, and structured work environment and remote work productivity using likerts-scale questions.